Relative importance of anthropogenic landscape characteristics for Neotropical frugivores at multiple scales - Nagy-Reis, M. B.; Estevo, C. A.; Setz, E. Z.F.; Ribeiro, M. C. [UNESP]; Chiarello, A. G.; Nichols, J. D. (Wiley, 2017)
Frugivores are key components of Neotropical forests, regulating plant communities, forest structure, and plant diversity; however, they are highly threatened by human impacts worldwide. To effectively conserve this group, maintain their ecological functions, and plan management actions or establish future protected areas, we need to gather information about their relationship with the landscape attributes. Here, we used camera traps and call surveys (April 2013 to March 2014) to estimate the occupancy of seven frugivores (a rodent, two ungulates, two primates and two ground-dwelling birds) at 45 sampling sites distributed within a protected area of Atlantic Forest (35 000 ha) in south-east Brazil. We evaluated the relative effects of anthropogenic landscape variables, environmental attributes and geomorphometry on their occupancy at multiple scales. To achieve this, we measured landscape metrics at three spatial scales (200, 500 and 1000 m) around each sampling site and used multi-season occupancy modeling. Factors related to human presence or disturbance, such as human accessibility, proximity to the reserve, and forest cover, were the main predictors of occupancy by frugivorous game species (paca – Cuniculus paca; brocket deer – Mazama sp.; and collared peccary – Pecari tajacu). Strictly environmental and geomorphometric variables were weaker determinants of frugivore occupancy. Our results also suggest that weather, season and habitat-related variables can equally influence animal detection probability. Moreover, different species of frugivores responded differently to landscape attributes, and their response depended on the spatial landscape scale at which they perceive their habitat. This highlights the importance of a multi-taxa and multi-scale approach when assessing species-habitat relationships and planning wildlife management actions.
Keywords: anthropogenic landscape; Atlantic Forest; call survey; camera traps; frugivores; multi-taxa; occupancy; protected areas